Formulation and Evaluation of Tofacitinib Nanosponges Incorportaed Tablet - Thakur, Gourav; Kumar, Sachin (Journal of Neonatal Surgery, 2025)
The present study aims on the formulated and analyze of a novel oral tablet formulation incorporating tofacitinib-loaded nanosponges aimed at enhancing solubility, bioavailability, and sustained drug release. Tofacitinib, a Janus kinase (JAK) inhibitor, is limited by poor aqueous solubility and rapid systemic clearance. To address these challenges, by using emulsion solvent diffusion method nano-sponges were develop with various polymers including Eudragit RL 30, Poloxamer 188, and ethyl cellulose. Among twelve formulations (T1–T12), formulation T3 was optimized based on particle size (127.4 nm), zeta potential (–25.4 mV), and highest entrapment efficiency (88.43%), polydispersity index (0.303). The optimized nanosponge (T3) was further compressed into tablets using direct compression. The tablet formulations (NT1–NT4) underwent pre-compression and post-compression evaluations including Carr’s index, angle of repose, content uniformity, hardness, friability, and in vitro dissolution. NT3 demonstrated excellent flowability, robust mechanical properties, and the highest drug release profile, reaching 90.12% over 12 hours, indicating a sustained release pattern. These findings suggest that nanosponge-incorporated tablets provide a promising platform for increased the performance of drug and patient compliant of tofacitinib in the treatment of autoimmune diseases.